CLIP‐COSY: A Clean In‐Phase Experiment for the Rapid Acquisition of COSY‐type Correlations. Issue 27 (19th May 2016) - Koos, Martin R. M.; Kummerlöwe, Grit; Kaltschnee, Lukas; Thiele, Christina M.; Luy, Burkhard
Abstract: The COSY experiment is an essential homonuclear 2D NMR experiment for the assignment of resonances. Its multiplet line shape, however, is often overly complicated, potentially leads to signal intensity losses, and is responsible for long minimum overall acquisition times. Herein, we present CLIP‐COSY, a COSY‐type experiment yielding clean in‐phase peaks. It can be recorded within a few minutes and benefits from enhanced signal intensities for most cross‐peaks. In combination with non‐uniform sampling, the experiment times can be further reduced, and the in‐phase multiplets enable the application of modern homonuclear decoupling techniques in both dimensions. As antiphase cancelations are avoided, CLIP‐COSY can also be applied to macromolecules and other samples with broadened lines. Abstract : A cozy COSY : The COSY experiment is one of the fundamental two‐dimensional NMR experiments. A severe drawback of state‐of‐the‐art implementations is the complex line shape, demanding long data acquisitions. Clean in‐phase COSY (CLIP‐COSY) combines the unique information from COSY experiments with a simple line shape (as in NOESY‐type spectra), and enables rapid acquisition and the combination with homonuclear decoupling.